Vacuum-Assisted Closure: A Novel Method of Managing Surgical Necrotizing Enterocolitis - Sea, Stephanie; Meckmongkol, Teerin; Moront, Matthew L.; Timmapuri, Shaheen; Prasad, Rajeev; Schwartz, Marshall Z.; Arthur, L. Grier (European Journal of Pediatric Surgery, 2015)
Purpose Necrotizing enterocolitis (NEC) requiring surgical intervention is associated with mortality rates approaching 50%. We evaluated outcomes of patients that underwent surgical treatment for NEC with vacuum-assisted closure (VAC) of the abdomen as compared with traditional laparotomy, bowel resection, and ostomy creation.Methods A retrospective review identified 26 patients from 2007 to 2012 with NEC. Overall, 17 patients were treated with laparotomy, and 9 were treated with laparotomy and VAC (LapVac). Age, weight, preoperative and postoperative mean airway pressure, length of bowel resected, duration on total peripheral nutrition, time until initiation of feeds, and length of stay were assessed. A Student's t-test was used for statistical analysis.Results Nine LapVac patients underwent a total of 1.2 ± 1.3 VAC changes and had open abdomens for 13.1 ± 19.1 days. LapVac and traditional laparotomy patients had similar outcomes with respect to amount of bowel resected, time on a ventilator, time to initiation of feeds, and length of hospital stay. Two of nine patients (22%) in the LapVac group were placed in continuity without the need for an ostomy. We identified a subset of patients in the LapVac group that demonstrated signs of abdominal compartment syndrome (ACS), exhibiting mean airway pressures greater than 15 cm H2O preoperatively. Patients with ACS treated with VAC therapy had shorter time to initiation of feeds (p = 0.047) and shorter lengths of stay (p = 0.0395) as compared with traditional laparotomy.Conclusion Our data demonstrate that use of the wound VAC is a safe approach in the management of premature infants with NEC requiring surgical intervention with outcomes comparable to standard surgical management. Use of the wound VAC may allow the establishment of bowel continuity and abdominal closure without the need for an ostomy. VAC therapy may also hasten the recovery of NEC patients with concomitant ACS by eliminating the compartment syndrome. Larger studies are required to confirm this theory.
Keywords: necrotizing enterocolitis; abdominal compartment syndrome; vacuum-assisted closure